2022
DOI: 10.1155/2022/7003809
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents and Antimycobacterial Activities of Root Extracts and Fractions from Vernonia glabra, (Steetz) Vatke

Abstract: Vernonia glabra is used by Malawian traditional healers to treat a myriad of ailments including shingles, diabetes, dysentery, diarrhoea, cough, wounds, gonorrhoea, and gastrointestinal problems. This study evaluated phytoconstituents and the in vitro antimycobacterial activities of the crude extracts and fractions from roots of Vernonia glabra. Agar disk diffusion and modified broth microdilution assays were used to determine the antimycobacterial activities of dichloromethane (DCM) and ethyl acetate (EtOAc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The ethyl acetate fraction of BS-16 was further characterized by FT-IR and GC–MS analysis. Through FT-IR, it was found that the phthalate compounds 1,2-benzenedicarboxylic acid, diisooctyl ester, phthalic anhydride, phthalic acid, and monoethyl ester were reported for antimicrobial activity . The closely related compound called dimethyl phthalate was found to deform the cell membrane and disrupt the membrane channels to induce antimicrobial activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethyl acetate fraction of BS-16 was further characterized by FT-IR and GC–MS analysis. Through FT-IR, it was found that the phthalate compounds 1,2-benzenedicarboxylic acid, diisooctyl ester, phthalic anhydride, phthalic acid, and monoethyl ester were reported for antimicrobial activity . The closely related compound called dimethyl phthalate was found to deform the cell membrane and disrupt the membrane channels to induce antimicrobial activity .…”
Section: Discussionmentioning
confidence: 99%
“…Through FT-IR, it was found that the phthalate compounds 1,2-benzenedicarboxylic acid, diisooctyl ester, phthalic anhydride, phthalic acid, and monoethyl ester were reported for antimicrobial activity. 42 The closely related compound called dimethyl phthalate was found to deform the cell membrane and disrupt the membrane channels to induce antimicrobial activity. 43 Similarly, the presence of these compounds in the BS-16 ethyl acetate extract could have disrupted the bacterial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…DIOP from marine brown algae Sargassum wightii was found to be an antimicrobial compound [62]. Similarly, DIOP was also identified as a phytochemical in Vernonia glabra root ethyl acetate extracts, which showed antitubercular activity against Mycobacterium tuberculosis [63].…”
Section: Identification Of Phytochemicals Using Gas Chromatography-ma...mentioning
confidence: 93%